Asymmetry Matters: Structure Elucidation and Application Potential of Solution-Processed Monoalkylated BTBT Thin Films - Hawly, Tim; Johnson, Manuel; Zhao, Baolin; Wu, Mingjian; Späth, Andreas; Streller, Fabian; Nickles Jäkel, Hannah; Halik, Marcus; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Electronic Materials, 2022)
Two-dimensionally (2D) extended thin films of p-type organic semiconductor C13-BTBT (BTBT = [1]benzothieno[3,2-b]-[1]benzothiophene) were fabricated via self-controlled growth at the liquid-liquid interface. Depicting a compound class originally developed for further functionalization and subsequent realization of self-assembled monolayers (SAMs), the potent BTBT core unit commonly excels in high-quality structure formation as well as charge-transport characteristics. Utilizing a manifold spectromicroscopic toolbox, we observe extraordinarily crystalline C13-BTBT films with an upright standing configuration of the backbone unit accounting for superior intermolecular orbital overlap. The well-defined morphology and internal structure of the film are being underpinned by charge-transport parameters that are in the range of comparable organic electronic devices based on bisubstituted BTBT films from the same processing technique. The inherently favorable membrane-like bilayer molecular arrangement is confirmed by unambiguous representation of the unit cell as derived from electron tomography.
CRIS-Team WoS Importer:2023-01-27

Employing x-ray spectromicroscopy for the understanding of anisotropy in organic thin film growth - Hawly, Tim; Späth, Andreas; Johnson, Manuel; Streller, Fabian; Watts, Benjamin; Raabe, Jörg; Fink, Rainer (AIP Conference Proceedings, 2023)
We report on the fabrication of high-quality organic semiconducting thin films from the potent benchmark molecular compounds pentacene and C8-BTBT-C8. For organic films prepared by the floating-lens method, we observe 1D anisotropy in linear NEXAFS dichroism. Based on the molecular orientation contrast in scanning transmission x-ray microspectroscopy (STXM), azimuthal sample rotation and AFM, we can confirm a high degree of long-range molecular order. The experimental results allow for deeper insight into the presumed growth behavior, which appears to crucially depend on the nature, or more specifically, the aromaticity and volatility, of the used solvent.
CRIS-Team Scopus Importer:2023-12-01

Exploring the Preparation Dependence of Crystalline 2D-Extended Ultrathin C8-BTBT-C8 Films - Hawly, Tim; Johnson, Manuel; Späth, Andreas; Nickles Jäkel, Hannah; Wu, Mingjian; Spiecker, Erdmann; Watts, Benjamin; Nefedov, Alexei; Fink, Rainer (ACS Applied Materials and Interfaces, 2022)
Crystalline organic semiconducting thin films from the benchmark molecule C8-BTBT-C8 were obtained using physical vapor deposition and various solution-based methods. Utilizing atomic force microscopy and X-ray spectromicroscopy, we illustrate the influence of the underlying growth mechanism and determine the highly preparation-dependent orientation of the thiophene backbone. We observe a continuous trend for crystalline C8-BTBT-C8 thin film domains to extend into the square millimeter-range under near-equilibrium growth conditions. For such well-defined systems, electron diffraction tomography allows us to precisely determine the unit cell directly after film deposition and to reveal an 8° molecular tilt angle with respect to the surface normal. This finding is in almost perfect accordance with the values derived from near-edge X-ray absorption fine structure linear dichroism. Within this work, we shine a light on both the successes and challenges connected to the realization of potent, thiophene-based semiconducting films, paving the way toward square centimeter-sized ultrathin organic crystals and their application in organic circuitry.
CRIS-Team Scopus Importer:2022-04-22
Keywords: 2D nanomaterials; electron tomography; molecular self-assembly; organic semiconductors; organic thin films; X-ray microspectroscopy

Field-induced modification of the electronic structure in BTBT-based organic thin films observed by NEXAFS spectroscopy - Johnson, Manuel; Hawly, Tim; Zhao, Baolin; Halik, Marcus; Nefedov, A.; Fink, Rainer (Applied Physics Letters, 2022)
We present an in operando near-edge x-ray absorption fine structure (NEXAFS) study on p-type [11-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)] BTBT-based self-assembled monolayer (BTBT-SAM) films. As a 2D-model system, the BTBT-SAM offers direct insight into the active organic semiconductor layer without interfering bulk materials. This allows for the observation of polaronic states caused by charged species at the dielectric/organic interface. Linear NEXAFS dichroism is employed to derive the molecular orientation of the BTBT subunit. Field-induced modifications in the unoccupied molecular orbitals are observed in the NEXAFS spectra. The spectral changes in the on- and off-states are discussed in the context of polaron formation due to charge accumulation induced by the applied electric field. Published under an exclusive license by AIP Publishing.
CRIS-Team WoS Importer:2022-12-02

Structural characterization of alpha,omega-DH6T monolayer films grown at the liquid-liquid interface - Johnson, Manuel; Hawly, Tim; Wu, Mingjian; Spiecker, Erdmann; Fink, Rainer (Soft Matter, 2021)
The molecular self-organization of alpha,omega-dihexylsexithiophene (alpha,omega-DH6T) monolayers prepared at the solvent-water interface is investigated by complementary microscopy techniques. Our study focuses on the influence of solvents and initial droplet volume on the resulting film morphology. Long-range extended domains in the monolayer regime are detected by visible light microscopy only for toluene. Small-area electron diffraction (SAED) proves the formation of single-crystalline monolayers with structural parameters identical to the organic bulk crystals. In comparison with conventional vacuum sublimated thin films a deviant molecular orientation, derived from near-edge-X-ray absorption fine structure (NEXAFS) in combination with a lower step height measured by atomic-force-microscopy (AFM), indicates a different behaviour of the flexible terminal hexyl chains during growth in a liquid surrounding. Furthermore, a structural degradation over time is observed which is caused by residual solvent molecules that are incorporated during the transfer procedure.
Created from Fastlane, WoS look-up

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics